Safety and Efficacy of Galactogogues: Substances that Induce, Maintain and Increase Breast Milk Production - Antonio Alberto Zuppa; Paola Sindico; Claudia Orchi; Chiara Carducci; Valentina Cardiello; Piero Catenazzi; Costantino Romagnoli; Piero Catenazzi (Frontiers Media S.A., 2010)
Poor production of breast milk is the most frequent cause of breast lactation failure. Often, physician prescribe medications or other substances to solve this problem. The use of galactogogues should be limited to those situations in which reduced milk production from treatable causes has been excluded. One of the most frequent indication for the use of galactogogues is the diminution of milk production in mothers using indirect lactation, particularly in the case of preterm birth. The objective of this review is to analyze to the literature relating to the principal drugs used as galactogogues (metoclopramide, domperidone, chlorpromazine, sulpiride, oxytocin, growth hormone, thyrotrophin releasing hormone, medroxyprogesterone). Have been also analyzed galactogogues based on herbs and other natural substances (fenugreek, galega and milk thistle). We have evaluated their mechanism of action, transfer to maternal milk, effectiveness and potential side effects for mother and infant, suggested doses for galactogogic effect, and recommendation for breastfeeding.